Recognition and Analysis of Pest-Induced Damage in Mangrove Ecosystems: A Case Study in Maros Coastal Region - Mappiasse, Muh Faisal; Mukhlisa , Andi Nurul; Mappiasse, Muh. Faisal M (Jurnal Wasian, 2024)
Mangroves in the coastal region of Maros Regency represent a critical ecosystem that plays a vital role in coastal protection, marine habitat provision, and climate change mitigation. However, these mangroves face numerous threats, including pest infestations that can severely damage the ecosystem. This study aims to (1) identify the types of pest attacks and the mangrove species affected in the coastal area of Maros Regency and (2) analyse the level of damage caused by these pest attacks. Using field observation methods, this research provides an in-depth analysis of mangrove damage resulting from pest infestations. The findings reveal several primary types of pest attacks, including leaf suckers, leaf-eating caterpillars, stem borers, and termites. The forms of damage include discoloured leaves, damaged shoots and leaves, open wounds, resin secretion, cracked stems, and broken or dead branches, with the severity ranging from mild to severe, depending on the mangrove species. This data is expected to serve as a foundation for better mangrove management strategies to mitigate pest-induced damage in Maros Regency.